HUBUNGAN NISBAH K/Ca DALAM LARUTAN TANAH DENGAN DINAMIKA HARA K PADA ULTISOL DAN VERTISOL LAHAN KERING - A Kasno; Abdul Rachim; Iskandar Iskandar; J. Sri Adiningsih (Jurnal Ilmu Tanah dan Lingkungan, 2004)
The objectives of this experiment were: (1) to study the effect of K and Ca fertilization on the dynamic of K, (2) to study the relationship between the dynamic of K in the soils with corn growth, and (3) to determine the optimum K requirement on different K/Ca ratio in the soil solution. Ultisol and Vertisol from the upland areas were used for the study. The determination of K and Ca dosage was based on the maximum soil sorption. The experiment was carried out in a greenhouse using the factorial randomized complete design with three replications. Four levels K dosage and three levels Ca dosage were applied in the experiment. The C-7 hybrid of corn was selected as an indicator plant. The result showed that adding K and Ca increased the dry weight of the plant in both Ultisol and Vertisol. In Ultisol, adding of K increased the amount of exchangeable Ca, Mg and K, and water-extracted K, whereas adding of Ca increased the exchangeable Ca and Mg and water-extracted K. The optimum K requirement for Ultisol was 58 mg kg-1 for K/Ca ratio <0.03 and 88 mg kg-1 for K/Ca ratio >0.03. In Vertisol, adding of K increased the exchangeable and water-extracted K, while adding of Ca increased both exchangeable and water-extracted Ca and Mg. The optimum K requirement was 55 mg kg-1 for the K/Ca ratio <0.03 and 171 mg kg-1 for the K/Ca ratio >0.03. Water extracted Ca and Mg showed a negative relationship with the K/Ca ratio both in Ultisol and Vertisol. The positive relationship between K/Ca ratios with water-extracted K was found in Ultisol, and with both exchangeable and water-extracted K in Vertisol. The increase of the K/Ca ratio increased the critical level of exchangeable K and water-extracted K. Keywords: K/Ca ratio, K dynamic, soil solution, Ultisol, upland, Vertisol